Thin Films and Glass–Ceramic Composites of Huntite Borates Family: A Brief Review - Elena A. Volkova; Daniil A. Naprasnikov; Nikolay I. Leonyuk (Crystals, 2020)
Rare-earth aluminum borates, RAl3(BO3)4 (where R = Y, Pr–Lu), are of great interest because of their attractive multifunctional properties, depending on their structure and composition. The combination of desirable physical and chemical characteristics makes them promising materials for lasers and nonlinear optics. Research focusing on RAl3(BO3)4 (RAB) compounds and their solids solutions has continued for more than five decades and has been reflected in numerous articles and several reviews. The last decade’s enhanced interest is being conducted towards epitaxial layers because of the availability of other possible applications, for instance, as scintillators, visible emitting phosphors or optical waveguides and waveguide lasers. On the other hand, the tendency of borate melts to form glasses makes them attractive for research of micro-crystallization processes in these systems and can be effortless towards finding relatively inexpensive optical glass–ceramic materials with similar composition as alternative components to laser systems. This article reviews the recent progress carried out hitherto on epitaxial layers and glass–ceramic composites of huntite-type rare-earth aluminum borates.